Reconstructing Maqasid-Based Welfare Indicators According to Athiyyah: Integrating Hifz al-Nafs and Hifz al-Mal into Multi-Level Governance - Erika Rishan; Neng Yani Nurhayani; Raden Rara Rita Erawati; Nurrohman Syarif (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
Conventional welfare state models tend to be fragmented and centred on material indicators, making them less responsive to the holistic welfare needs of Muslim communities. This article aims to reconstruct a Maqasid Athiyyah-based welfare indicator framework by integrating hifz al-nafs and hifz al-mal within multi-level governance. The study adopts a qualitative-conceptual approach through literature synthesis and policy document analysis. Findings show that Maqasid as a normative anchor can strengthen policy coherence at micro, meso, and macro levels. At the micro level, a holistic empowerment pathway integrates basic guarantees, Islamic financial literacy, and psychospiritual assistance. The meso level transforms charitable philanthropy into ta’awun-based economic stability instruments through Islamic cooperatives. At the macro level, the Maqasid-Based Policy Impact Assessment (MB-PIA) evaluates material welfare, distributive justice, and social cohesion. The study concludes that Maqasid Athiyyah offers a coherent, measurable, and holistic welfare governance model supported by political commitment, institutional capacity, and cross-sector coordination.